Provision of universal broadband service in Japan: A policy challenge toward a sustainable ICT infrastructure - Hitoshi Mitomo (International Telecommunications Society (ITS), 2014)
This presentation outlines a proposal for a new frame work for the provision of universal service aimed at solving the various issues inherent in community informatization, and goes on to look at the advantages and disadvantages of the proposed framework and review its feasibility. In order to ensure that telecommunications services are universally accessible, in less favored areas, universal service is currently provided for analog landline telephones by using a universal service fund system to supplement a portion of costs of the qualified telecommunications carriers. With the development of optical networks, optical IP phones have also been included as a technology for which universal service is provided, but at the same time dependence on land line phones is decreasing due to the popularity and convenience of cell-phones. As this is accompanied by developments such as the fact thatalmost100%of Japanese households now have broadband access, there is a pressing need for radical review of the system from a technical perspective. Additionally, given that consumers' organizations and other bodies strongly oppose the fact that carriers pass on the burden of their universal service fund contributions so that the full amount of contributions is shared between telephone number users, it is also necessary to reconsider the approach to how cost burdens are shared. At the same time, while 2.5GHzbandregionalBroadband Wireless Access (BWA)has been made available for providing broadband in rural areas, its level of usage is low and ensuring its utilization is a matter of urgency. This presentation will deal with these issues collectively, and propose a framework for maintaining and developing community informatization.
Keywords: 330; Universal service; less favored areas; community informatization; regional broadband; regional BWA